Convective heat transfer in porous media - Mahmoudi, Yasser; Hooman, Kamel; Vafai, K. (Kambiz) (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Focusing on heat transfer in porous media, this book covers recent advances in nano and macro' scales. Apart from introducing heat flux bifurcation and splitting within porous media, it highlights two-phase flow, nanofluids, wicking, and convection in bi-disperse porous media. New methods in modeling heat and transport in porous media, such as pore-scale analysis and Lattice-Boltzmann methods, are introduced. The book covers related engineering applications, such as enhanced geothermal systems, porous burners, solar systems, transpiration cooling in aerospace, heat transfer enhancement and electronic cooling, drying and soil evaporation, foam heat exchangers, and polymer-electrolyte fuel cells.
Section I: Fundamentals of Convection in Porous Media 1. Introduction to Fluid Flow and Heat Transfer in Porous Media [Meysam Nazari, Yasser Mahmoudi, and Kamel Hooman] 2. Natural Convection in Porous Media [Kamel Hooman and Donald A. Nield] 3. Forced Convection in Porous Media [Pourya Forooghi and Benjamin Dietrich] Section II: Advanced Topics of Convection in Porous Media 4. Convective Heat Transfer of Nanofluids in Porous Media [Bernardo Buonomo, Davide Ercole, Yasser Mahmoudi, Oronzio Manca, and Sergio Nardini] 5. Pore-Network Simulation of Drying of Heterogeneous and Stratified Porous Media [Hassan Dashtian, Nima Shokri, and Muhammad Sahimi] 6. Wicking of Liquids under Non-Isothermal and Reactive Conditions: Some Industrial Applications [Mohammad Amin Faghihi Zarandi, and Krishna M. Pillai] 7. Thermal Effect on Capillary Imbibition in Porous Media [Jianchao Cai, Wei Wei, and Yasser Mahmoudi] 8. Convection in Bi-Disperse Porous Media [Arunn Narasimhan] 9. Pore Scale Analysis in Forced Convection Heat Transfer in Porous Media [Hasan Celik, Moghtada Mobedi, and Akira Nakayama] 10. Lattice Boltzmann Method for Modeling Convective Heat Transfer in Porous Media [Gholamreza Imani and Kamel Hooman] Section III: Advanced Engineering Applications of Convection in Porous Media 11. Modeling Thermohydraulic Process in Enhanced Geothermal System Based on Two-Equation Thermal Model for Porous Media [Wenbo Huang, Wenjiong Cao, Guoling Wei, Yunlong Jin, and Fangming Jiang] 12. Mixed Convection and Radiation Heat Transfer in Porous Media for Solar Thermal Applications [Simone Silvestri and Dirk Roekaerts] 13. Transpiration Cooling Using Porous Material for Hypersonic Applications [Adriano Cerminara, Ralf Deiterding, and Neil D. Sandham] 14. Thermal Management and Heat Transfer Enhancement Using Porous Materials [Cong Qi, Kuo Huang, Jiaan Liu, Guohua Wang, and Yuying Yan] 15. Metal Foam Heat Exchangers [Simone Mancin] 16. Heat and Fluid Flow in Porous Media for Polymer-Electrolyte Fuel Cells [Prodip Kumar Das and Deepashree Thumbarathy] 17. Combustion in Porous Media for Porous Burner Application [Muhammad Abdul Mujeebu]
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Engineering / Mechanical; SCIENCE / Chemistry / Industrial & Technical; Heat -- Convection; Mass transfer; Porous materials -- Thermal properties; Porous materials -- Permeability